Predicted magnitude of alternate access in the contemporary transcatheter aortic valve replacement era. Issue 5 (18th July 2018) - Rogers, Toby; Gai, Jiaxiang; Torguson, Rebecca; Okubagzi, Petros G.; Shults, Christian; Ben‐Dor, Itsik; Satler, Lowell F.; Waksman, Ron
Abstract: Objectives: We aimed to evaluate the true extent of alternate access in a contemporary cohort of transcatheter aortic valve replacement (TAVR) patients. Background: Appropriate access selection for TAVR impacts clinical outcomes. Despite device miniaturization, some patients remain ineligible for transfemoral arterial access. Methods: Five hundred seventy‐five consecutive TAVR patients were classified according to iliofemoral artery diameters measured by computed tomography (<5.0 mm, 5.0‐5.4 mm, 5.5‐5.9 mm, or ≥6 mm) and need for alternate access rate was estimated according to commercially available transcatheter heart valve Instructions For Use (IFU). Results: Based on iliofemoral artery diameters alone, 11.5% of patients were predicted to require alternate access. After patient‐level adjustment for the size of the planned THV and severe tortuosity or severe calcification, 14.9% and 20.8% of patients, respectively were predicted to require alternate access. Overall, 87.8% of patients underwent transfemoral TAVR and 12.3% underwent alternate access. There was no difference in the rate of major vascular complications and life threatening or major bleeding between groups, but transfusion rate was higher in smaller vessel groups. Conclusions: Despite device miniaturization, a substantial minority of contemporary TAVR patients still require alternate access. Most are eligible for newer extrathoracic approaches including transcaval, subclavian, and transcarotid that avoid the morbidity of transthoracic access.